Engaging departments : (Anker Publishing, 2006)
This book fills an important niche in the literature on institutional engagement and advances the national Campus Compact agenda to create engaged departments. Representing a range of disciplines—art, Chicana and Chicano studies, communication, educational psychology and counseling, English, geology, nursing, social work, sociology and anthropology—and institution types—two-year and four-year, public and private, comprehensive and research—the heart of this work features 11 departments and their journeys to engagement, focusing on transferable steps and strategies, key factors that helped move civic engagement from the individual faculty level to the collective department level, successes and barriers, and future visions. Also outlined are engagement efforts at the institutional and state system levels.